(untitled) (Journal of the College of Education for Women, 2019)
Present research is aimed knowing of smart thinking for secondary schools’ students. and discover statistically significant differences in Smart Thinking due to the couple variables of (Gender – Branch)For the purpose of verification of the aims of the research, the researcher has prepared a smart thinking scale, the scale has been applied on sample of secondary schools’ students for both Branches (Scientific & Literary One).It was contingent (500) student male and female were chosen stratified random method.After data analyze the reached results: The Preparatory fourth grade students have smart thinking. Female smart thinking enjoy a much higher degree than males. and Scientific branch students enjoy thinking and much higher degree of smart literary Branch studentsIn light of these results the researcher put forward a number of recommendations including: Developing school curricula in better methods by the addition of new items that helps students to effective learning and thinking to keep up with smart cognitive development , The development of teaching aids and emphasis on the use of modern methods that contribute to stimulate the minds of students. And the proposals: Conducting a similar study on a sample of students (National School, Non-Governmental schools)